Benefits of curcumin in brain disorders. (11th June 2019) - Bhat, Abid; Mahalakshmi, Arehally M.; Ray, Bipul; Tuladhar, Sunanda; Hediyal, Tousif A.; Manthiannem, Esther; Padamati, Jagadeeswari; Chandra, Ramesh; Chidambaram, Saravana B.; Sakharkar, Meena K.
Abstract: Curcumin is widely consumed in Asia either as turmeric directly or as one of the culinary ingredients in food recipes. The benefits of curcumin in different organ systems have been reported extensively in several neurological diseases and cancer. Curcumin has got its global recognition because of its strong antioxidant, anti‐inflammatory, anti‐cancer, and antimicrobial activities. Additionally, it is used in diabetes and arthritis as well as in hepatic, renal, and cardiovascular diseases. Recently, there is growing attention on usage of curcumin to prevent or delay the onset of neurodegenerative diseases. This review summarizes available data from several recent studies on curcumin in various neurological diseases such as Alzheimer's disease, Parkinson's disease, Multiple Sclerosis, Huntington's disease, Prions disease, stroke, Down's syndrome, autism, Amyotrophic lateral sclerosis, anxiety, depression, and aging. Recent advancements toward increasing the therapeutic efficacy of curcuma/curcumin formulation and the novel delivery strategies employed to overcome its minimal bioavailability and toxicity studies have also been discussed. This review also summarizes the ongoing clinical trials on curcumin for different neurodegenerative diseases and patent details of curcuma/curcumin in India.